Pengaruh Penggunaan Limbah Polyethylene Terephthalate (PET) Terhadap Karakteristik Marshall pada Campuran AC-BC - Ningrum, Puspa; Basri, Doni Rinaldi; Oki, Jeni (Sekolah Tinggi Teknologi Pekanbaru, 2024)
Nowadays, the presence of plastic waste is increasing. This is because the use of plastic as a material for packaging food and drinks has not yet been replaced. This is why researchers are concerned about the accumulation of polyethylene terephthalate (PET) plastic waste at the location of road construction projects which originates from workers' daily consumption of food and drinks. So it is felt necessary to use PET plastic waste as an additional or substitute material for asphalt mixtures that is environmentally friendly and economical, because PET plastic contains polymers that are plastomers. In this research, various levels of PET plastic waste were used: 0%, 4%, 4.5%, 5%, 5.5%, 6%. The research results concluded that the use of 4.5% PET plastic waste in the AC-BC mixture had marshall characteristic values ??that requirements. The optimum asphalt content value is 5.7% with Marshall properties including a stability value of 1,235.1 Kg, a flow value of 3.03 mm, 409.41 Kg/mm of Marshall Qoutient (MQ) value, 15, 62% of VMA, 72.19% of VFA, and 4.34% of VIM.